Contested Subjectivities in Textual and Visual Representations of Jacob Zuma - Makupula, Siwongiwe Chumani (University of the Witwatersrand, Johannesburg, 2024)
This MA research report studies visual, textual and musical portrayals of former South African president, Jacob Zuma. The study was undertaken through an analysis of material categorised into three genres: biography, music, and visual culture. In the category of biography, I looked at Jeremy Gordin’s Zuma: A Biography (2006) and Redi Tlhabi’s Khwezi: The Remarkable Story of Fezekile Ntsukela Kuzwayo (2017). I was particularly interested in the ways Zuma’s public rape trial is presented as an obstacle in Gordin’s Zuma and as a centripetal force in Tlhabi’s Khwezi. From this, I demonstrated the ways these representations of Zuma map gender constructions in South African politics. With music, I was interested in the ways the former president uses struggle songs to construct an image of victimhood while reminding the public about his personal sacrifices in South Africa’s armed struggle I further looked at the ways maskandi music, through ethnonationalist logics, endorsed a “militant” Zuma. Lastly, I looked at Zuma as a heroic figure in amapiano and the ways that communicates Black exigencies in peri-urban South Africa. In the last category, visual culture, I looked at the slipperiness of parody in a country overdetermined by a history of racial tension. I explore the strengths of the portraits and where they offer poignant criticism of the former president. Three of the four portraits are inspired by the predatory sexuality covered in the first chapter while one, “Umshini Wam” is inspired by opportunist and self-serving practices of Zulu culture explored in the chapter on music. I demonstrate that even with these conditions, the erect Black penis is inadvertently harmful. As this should suggest, the three chapters outline three different paradigms to conflicts of subjectivity in post-apartheid South Africa. The first chapter takes a gender studies approach to map violent masculinity performances while trying to locate the place of women in these spectacular displays of [ethno] nationalism. The second chapter, where we study visual portrayals, focuses on class and race as the guiding categories of analysis. We argue that with South Africa’s complicated and violent colonial then apartheid history, racialized exchanges are inevitably charged with a range of discourses. This chapter argues that the “rainbow-nation” narrative prevents South Africans from meaningful engagement with histories of racial and economic formations and this lack manifests itself in negative social exchanges that are inadvertently harmful and potentially retraumatizing. In the final chapter, our guiding paradigm is ethno-cultural codes of social organizing. These guiding or dominant paradigms do not exist 6 exclusively as is evident in the final chapter where gender is an operative category in tandem with ethnic and class subjectivities. As such, this report argues that these categories infuse each other and manifest as complicated mixtures in all three genres studied.
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Jacob Zuma; Textual and Visual Portrayals; Popular Culture; Biography; Masculinities; SDG-4: Quality education